Effect of Confinement on Thermal Performance of Two-Phase Closed Thermosyphon - 강석경 (The Graduate School, Ajou University, 2024)
Two-phase closed thermosyphon (TPCT) is a latent heat-based high-efficiency heat transfer device, primarily utilized in heat pipe heat exchanger (HPHX) in waste heat recovery (WHR) applications. Recently, there has been increasing interest in small diameter TPCT due to thermal confinement issues and space and cost limitations of heat transfer devices. Since 2018, many studies on HPHX have been using small diameter TPCT with an inner diameter of less than 10 mm. The nature of the two-phase flow characteristics and thermal performance of a small diameter thermosyphon are different from those of a large diameter one (inner diameter about 1 inch), and it is called the "confinement effect" of TPCT. The inner diameter and type of working fluid significantly affect the confinement of thermosyphon, but their effects remain unclear. In this study, the internal flow and heat transfer characteristics due to confinement effects were experimentally explored with TPCTs with inner diameters of 5 to 25 mm. Based on the Laplace length, which means the characteristic bubble size, four working fluids were considered: water, acetone, ethanol, and the HFE-7000. As a result, from the visualization results, the "Confined" TPCT was defined as when a counter-gravity flow occurred, where the liquid condensate falling along the TPCT wall was pushed up by the shear stress caused by the upward vapor flow, and the liquid was lifted up to the condenser. The confinement of TPCT was classified as "Intermittent confined", "Consecutive confined", and "Fully confined" according to the degree of confinement effect. In relation to the confinement type, the flow characteristics inside the TPCT were discussed in detail according to the inner diameter, the type of working fluid, and the operating heat flux. TPCT thermal performance, which is closely related to flow characteristics, was also discussed in detail. First, it was compared the thermal performance according to the working fluid, and found that the higher the figure of merit (FOM), the lower the thermal resistance. However, the water-filled TPCTs showed poor thermal performance despite the highest FOM at low heat flux conditions due to the very high latent heat of vaporization. Secondly, the thermal performance depending on the inner diameter was investigated, specifically the thermal resistance of TPCT and heat transfer coefficient at each section. Thermal performance was strongly related to the type of confinement, especially when the TPCT was “Consecutive confined” or “Fully confined”, with very poor thermal performance. Finally, the criteria for the stable operation of TPCT were presented. The results showed that TPCT could operate normally with minimal effect of confinement, with Co and Fr both below 0.3. The results of this study are expected to significantly contribute to a clear understanding of the operation nature of compact TPCTs.
학위논문(박사)--기계공학과,2024. 8
Keywords: Two-phase closed thermosyphon; confinement effect